Sequencing and Analysis of Fungal rRNA Operons for Development of Broad-Range Fungal PCR Assays - Khot, Prasanna D. (American Society for Microbiology (ASM), 2009)
rRNA genes are attractive targets for developing PCR assays targeting human fungal pathogens. Most studies have focused on the 18S rRNA gene, internal transcribed spacers, and the 5′ end of the 28S rRNA gene. An approximately 2,900-bp region of the 28S rRNA gene remains largely unexplored because sequences of many medically relevant fungi are either unavailable or undefined in genomic databases. The internal transcribed spacers and 28S rRNA gene of nine medically and phylogenetically important fungi were sequenced. In addition, 42 sequences from this region were acquired from public databases, resulting in an alignment of 51 fungal sequences spanning 30 fungal genera. For the nearly 3,950-bp region from the 3′ end of 18S rRNA gene to the 3′ end of the 28S rRNA gene, 27 broad-range PCR primers were designed such that their sequence homology with the human rRNA gene was minimal. All 62 possible amplicons in the size range from 75 to 400 bp from 27 primers were screened using fungal genomic DNA from 26 species spanning 14 genera. Eleven of the 62 amplicons did not cross-react with 1 μg/PCR human DNA but simultaneously amplified 10 fg of fungal DNA. Phylogenetic distance matrices were calculated for regions covered by these 11 amplicons based on 51 fungi. Two of these 11 amplicons successfully amplified 30 fg of fungal DNA from 25 of 26 fungi and provided the most phylogenetic information for species identification based on the distance matrices. These PCR assays hold promise for detection and identification of fungal pathogens in human tissues.